The Effect of Papaya Fruit Consumption (Carica Papaya L) on Increasing Breast Milk Production in Breastfeeding Mothers - Nissa Agustya; Lili Farlikhatun (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Exclusive breastfeeding during the first 6 months of a baby's life still has many obstacles. One of the obstacles that are often encountered is the lack of milk production. Various ways are done by postpartum mothers in increasing breast milk, one of which is by consuming foods that contain lactagogum. Papaya is one of the fruits available throughout the year in Indonesia and is believed to increase breast milk production. The purpose of this study was to determine the effectiveness of giving and consuming papaya fruit on increasing breast milk production. The design of this study was an experimental quasy. The location used for this research is in the working area of the UPT Puskesmas Petir Serang Regency, Banten Province from June to July 2023. The sample used in this study was 30 people. The intervention is the administration of young papaya fruit to be consumed at least 600 grams in 1 day and given in 7 days. The bivariate analysis used is chi square. Based on the results of chi-square analysis, the odds ratio value (OR: 2.98; 95% Confident Interval 1.04 – 8.52; p value 0.035).